PROMOTION OF A POSITIVE LEARNING ENVIRONMENT - Barbosa de Sousa, Leilane; Ferreira Moura, Escolástica Rejane; Teixeira Barroso, Maria Grasiela (Investigación y Educación en Enfermería, 2009)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> Objective: to relate the promotion of a positive learning environment experience. Methodology: descriptive study with the theoretical and methodological approaches of the Reference Manual for Formation of Teachers Johns Hopkins Program for International Education in Reproductive Health, United States of America. An expositive class was developed by a master’s student (with the orientation of teachers of the “Methodology of Nursing” course) with the participation of 28 students and the incumbent teacher of the “Psychology applied to Health” course. The experience happened in November, 2006. Results: The participants expressed acceptance to the method and pointed out important aspects of a positive learning environment, such as dominance and confidence, dynamism in the oral presentation, opportunity forparticipation, practical application and summary of main points. Conclusion: the results focused the importance to review traditional educational paradigms considering the standpoint of the students, who are the protagonists of the process.